2012
DOI: 10.1021/ac300185j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Deposition Order of Overlapping Latent Fingerprints and Inks Using Secondary Ion Mass Spectrometry

Abstract: A new protocol using time-of-flight secondary ion mass spectrometry (ToF-SIMS) has been developed to identify the deposition order of a fingerprint overlapping an ink line on paper. By taking line scans of fragment ions characteristic of the ink molecules (m/z 358.2 and 372.2) where the fingerprint and ink overlap and by calculating the normalised standard deviation of the intensity variation across the line scan, it is possible to determine whether or not a fingerprint is above ink on a paper substrate. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…This may be useful when a fingerprint is smudged or details of the donor are not contained within the fingerprint database. Many techniques have been proposed for these applications, including spectroscopic techniques [30], which lack the selectivity of mass spectrometry methods; chromatography based approaches [22,29] which require considerable sample preparation and consume at least an entire fingerprint; and vacuum based methods [20][21][22][23][24][25], which have lower sample throughput and have been shown to degrade fingerprint chemistry [31].…”
Section: Introductionmentioning
confidence: 99%
“…This may be useful when a fingerprint is smudged or details of the donor are not contained within the fingerprint database. Many techniques have been proposed for these applications, including spectroscopic techniques [30], which lack the selectivity of mass spectrometry methods; chromatography based approaches [22,29] which require considerable sample preparation and consume at least an entire fingerprint; and vacuum based methods [20][21][22][23][24][25], which have lower sample throughput and have been shown to degrade fingerprint chemistry [31].…”
Section: Introductionmentioning
confidence: 99%
“…The imaging mass spectrometry (IMS) technique for visualizing the spatial distribution of biological tissues and cells is a relatively recent development [1][2][3]. There are two techniques, secondary ion mass spectrometry (SIMS) and matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) that are widely used in IMS investigations.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the Cooks group [34] that originally developed this technique showed that DESI MS can be used for the chemical imaging of endogenous components such as cis-hexadec-6-enoic acid, stearic acid, cis-octadec-8-enoic acid, palmitic acid, pentadecylic acid, myristic acid, and triacylglycerols in sebumrich LFPs, as well as small amounts of illegal drugs such as cocaine and THC, and explosives such as RDX in contaminated LFPs. Recently, chemical imaging techniques utilizing surface-assisted laser desorption/ionization time-offlight MS (SALDI-TOF-MS) and matrix-assisted laser desorption ionization MS (MALDI-MS) have significantly improved the study of fingerprint composition because of their ability to identify and map the substances present in LFP residues [50][51][52][53][54][55]. Most studies are devoted to finding new substances that are capable of increased photon-energy absorption from the incoming laser in place of traditional matrixes.…”
Section: Mass Spectrometrymentioning
confidence: 99%